Metode Alternatif Menentukan KPK dan FPB Suatu Bilangan Bulat dengan Menggunakan Alat Peraga - Nurul Astuty Yensy (University of Bengkulu, 2020)
Mathematics has an important role in the world of education because it is very supportive of knowledge in other fields, such as physics, chemistry, biology and science. However, most people consider mathematics to be very difficult and boring because it is abstract, so mathematics learning should be carried out in a fun and interesting manner and easily understood by students. Determining the KPK and FPB of an integer is one of the mathematical material that is often considered difficult by students in primary school, especially if the number is large enough. Usually the teacher uses a factor tree or prime factorization. It was never applied using props, so this article discusses the alternative methods of determining the KPK and FPB of an integer using the props. The visual aids used were KPK and FPB boxes. Through this teaching aid, the learning becomes more fun and students become more enthusiastic about learning and understanding the concept of material becomes more increased.